High Molecular Weight Polystyrene Obtained by Cationic Emulsion Polymerization Catalyzed by Imidazolium‐Based Ionic Liquid. Issue 2 (30th November 2018) - Patrocinio, Vinicius M. B.; Agner, Tamara; Dutra, Gabriel V. S.; Machado, Fabricio; Neto, Brenno A. D.; Araújo, Pedro H. H.; Sayer, Claudia
Abstract: The ionic liquid 1‐ n ‐butyl‐3‐methylimidazolium heptachlorodiferrate (BMI.Fe2 Cl7 ) is efficiently used as catalyst in the cationic emulsion polymerization of styrene. The effect of different reaction temperatures, surfactant, and ionic liquid concentrations on polymer properties as molecular weight distribution and particle size is evaluated. High weight average molecular weights, above 1000 kDa, are achieved at 70% of conversion in 100 nm polystyrene particles formed mainly by micellar nucleation. Particle sizes and molecular weights increase with the decrease of the amount of surfactant. Even at low concentrations, BMI.Fe2 Cl7 /styrene molar ratio equal to 1/1000, the ionic liquid proves to be efficient for the emulsion polymerization of styrene, and lower ionic liquid concentrations lead to the formation of longer polymer chains. Abstract : A novel synthesis route to produce high molecular weight polystyrene, with M w around 1 000 000 Da, via the cationic emulsion polymerization of styrene using the ionic liquid 1‐ n ‐butyl‐3‐methylimidazolium heptachlorodiferrate (BMI.Fe2 Cl7 ) as a water tolerant catalyst is presented.